CONTENT AND CHARACTERISTICS OF THE CONCEPT OF NATIONAL AND RELIGIOUS VALUES - Dilfuza Pardaboeva, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The rapid development of socio-economic processes not only seeks optimal ways to solve global problems of mankind, but also develops issues such as the preservation of material and spiritual values ​​and their transmission to future generations, the study of national and religious values.